Beyond the Loop: Accountability and the Legal Abyss of Autonomous Weapon Systems - Khalil, Ahmad; S, Anandha Krishna Raj (Indonesian Journal of International Law, 2026)
The emergence of autonomous weapon systems (AWS) poses unprecedented challenges to international humanitarian law (IHL), particularly in relation to criminal responsibility. This article critically examines the existing legal vacuum concerning accountability for violations committed by AWS in the context of armed conflict. By analyzing the fluid and evolving nature of military autonomy and the consequences of removing human oversight from lethal decision-making processes, the article undertakes an in-depth assessment of international criminal law (ICL) mechanisms, including direct and command responsibility. It demonstrates the inadequacy of established legal doctrines to attribute criminal liability to designers, programmers, operators, or commanders when AWS operate through autonomous decision-making. The article further highlights the unreliability and unpredictability of AWS, especially in offensive warfare, and questions whether current criminal law standards are capable of addressing the complexity introduced by machine-directed hostilities. Engaging with theoretical constructs such as moral programming and joint criminal enterprise, the analysis concludes that, in the absence of a universally agreed definition and a comprehensive international regulatory framework, meaningful accountability remains beyond reach. The article ultimately calls for urgent international cooperation and innovative developments in criminal law to safeguard human rights and uphold the fundamental principles of IHL in the age of autonomous warfare.